Metode Field Trip Berbasis Virtual Reality pada Pembelajaran Menulis Puisi Sebuah Desain Pembelajaran Digital di Era Kurikulum Merdeka: Virtual Reality Based Field Trip Method in Poetry Writing Learning A Digital Learning Design in the Era of Merdeka Curriculum - Aswan, Aswan; Harsiati, Titik; Widyartono , Didin (Journal of Smart System, 2023)
Several studies indicate that the poetry writing abilities of learners in Indonesia tend to be dull and fail to capture learners' attention. The primary issue observed is the use of inadequate and monotonous teaching methods. Based on this phenomenon, the author presents a conceptual idea by integrating the use of field trip methods with virtual reality into poetry writing education. The purpose of this conceptual idea is rooted in the current educational cultural development in Indonesia, which emphasizes digitalization aspects that align with the independent curriculum. From the conducted results and discussions, it was discovered that the integrated field trip method with VR operates through syntax within poetry writing instruction. Four syntax components were modified: preparation activities, implementation activities, core activities, and closing activities. Through these modifications, VR serves as a medium that constructs learners' comprehension of poetry writing activities, from generating ideas to creating the final piece. This conceptual idea aligns with the development of the Indonesian curriculum, which embraces independent learning. The conclusion drawn is that the field trip method can be applied as an interactive teaching approach for poetry instruction within the context of independent learning. A limitation of this study is its lack of effectiveness testing, which warrants recommendations for future researchers.